Explorando la teoría de motivación de Herzberg: Una revisión teórica de su impacto en aspectos valorados por las organizaciones - Gibu La Torre, Yanira (2024)
Work motivation is a topic that, over the years, continues to be considered important, as it can help organizations to have workers with the desire to achieve their goals and, thus, contribute to the growth of the organization. There are various motivation theories that have emerged, including Herzberg's theory, which can be applied today through its motivational and hygiene factors. The objective of this paper is to explain this theory and demonstrate that its factors have an impact on aspects valued by organizations. To do so, different papers related to the topic were reviewed, finding out that there is an impact on aspects such as staff turnover, absenteeism, work environment, job performance and productivity if both factors are implemented in organizations. The conclusion was that the motivational factors that have an impact are recognition, the work itself, responsibility, progress, growth, achievement. The hygiene factors that have an impact are working conditions, salary, security, company policy and administration, personal life, relationships with supervisors and colleagues.